Infecção ativa pelo Citomegalovírus, em pacientes transplantados renais, detectada pela PCR em Tempo Real - Araujo, Ilana Farias Ribeiro (2023)
The cytomegalovirus (CMV) is a highly prevalent virus worldwide. On transplanted pacients, he’s the most common agent of infection with 20 to 60% of incidence and mortality reaching 90%. The emergence of infections in the post-transplant period is determined by serological profile of the pair donor/recipient. The study was cross-sectional, retrospective and quantitative attended 132 patients undergoing renal transplantation at University Hospital Walter Cantídio (HUWC) of the Federal University of Ceará, who carried out the research CMV by PCR in real time, from January to December 2012. The analysis was made for the prevalence of CMV pair donor / recipient showing that most receivers (85.6%) and their donors (87.9%) were seropositive for CMV before the transplant. The 132 recipients were distributed according to the serology for CMV pair of Donor / Receiver before the transplant. The majority (n = 99, 75%) of the 132 recipients is in Group 2 (D + / R +), formed by HIV-positive receptors for CMV seropositive donors that transplanted. The induction therapy Thymoglobulin was performed in 77 (58.3%) and Basiliximab in 49 (37.1%) of the 132 receptors. In six patients could not be determined induction therapy. Rejection episodes were observed in 17 (12.9%) of the 132 recipients, 15 (88.2%) in group 2 receptors (D + / R +) and 2 (11.8%) in group 1 (D + / R- ). Most receivers (62.1%) perfomed dialisys after transplantation. However, a greater number of dialysis patients in Group 2 was observed (D + / R +) compared with the 3 groups. CMV DNA copies were detected in 26 (19.7%) of the 132 recipients, mean ± 567,235.00 2,231,948.00 copies of DNA / mL of CMV. Increased number of CMV DNA copies was found in Group 2 (D + / R +) compared to Group 1 (D + / R-). However, only 13 (50%) of the 26 patients had CMV DNA copies with "cut-off" above 2,000, considered by the manufacturer with active CMV infection, and 2 patients in group 1 and 11 (45.8% ) of the 24 patients in Group 2. CMV disease was observed in 12 (9.1%) of the 132 patients evaluated, 10 (83.3%) patients in Group 2 (D + / R +) and 2 (16.7%) in group 1 (D + / R- ). Our results reinforce the need for the monitoring of viral load by real-time PCR in moderate-risk patients for the development of CMV disease (group 2) and the adoption of preemptive therapy in those with active infection.